Soil compounding promotes the improvement of aeolian sandy soil in the Mu Us Sandy Land - Chen, Shichao; Chen, Xue; Zuo, Hejun; Yan, Min; Wang, Haibing; Li, Xiaole (Frontiers in Environmental Science, 2024)
This study employed aeolian sandy soil and loess soil of the Mu Us Sandy Land as the research material to investigate the effect of soil compounding on the improvement of aeolian sandy soil and to provide a feasible approach for sand prevention and sand control. In particular, loess soils were compounded at 0%, 20%, 40%, 60%, 80%, and 100% by volume percentage of the compounded soils, respectively. The improvement benefits of compounded soils on their textural properties, water-holding capacity, and fertilizer retention capacity at different blending ratios were evaluated. The results showed that following the compounding of aeolian sandy and loess soils, with the increase of the loess proportion, the texture type of the compounded soil transforms from sandy soil to loamy sandy soil to sandy loam to loamy soil to powdery loam . Moreover, granular gradation was observed, the bulk density gradually decreased, the capillary porosity gradually increased, and the performance of water- and fertilizer-holding properties gradually increased and strengthened. The spatial variability of compounded soil bulk density, capillary porosity, and the water-holding and fertilizer retention properties were almost entirely controlled by the proportion of loess soil. This study provides a theoretical basis for aeolian sandy soil improvement in the Mu Us Sandy Land that can be extended to similar areas, providing a feasible sand management approach.